Changes in Cerebral Blood Flow during an Alteration in Glycemic State in a Large Non-human Primate (Papio hamadryas sp.) - Kochunov, Peter; Wey, Hsiao-Ying; Fox, Peter T.; Lancaster, Jack L.; Davis, Michael D.; Wang, Danny J. J.; Lin, Ai-Ling; Bastarrachea, Raul A.; Andrade, Marcia C. R.; Mattern, Vicki; Frost, Patrice; Higgins, Paul B.; et al. (Frontiers in Neuroscience, 2017)
Changes in cerebral blood flow during a hyperglycemic challenge were mapped, using perfusion-weighted MRI, in a group of nonhuman primates. Seven female baboons were fasted for 16 hours prior to one-hour imaging experiment, performed under general anesthesia, that consisted of a 20-min baseline, followed by a bolus infusion of glucose (500mg/kg). Cerebral blood flow maps were collected every seven seconds and blood glucose and insulin levels were sampled at regular intervals. Blood glucose levels rose from 51.3±10.9mg/dL to 203.9±38.9mg/dL and declined to 133.4±22.0mg/dL, at the end of the experiment. Regional cerebral blood flow changes consisted of four clusters: cerebral cortex, thalamus, hypothalamus and mesencephalon. Increases in the hypothalamic blood flow occurred concurrently with the regulatory response to systemic glucose change, whereas cerebral blood flow declined for other clusters. The return to baseline of hypothalamic blood flow was observed while cerebral blood flow was still increasing in other brain regions. The spatial pattern of extra-hypothalamic cerebral blood flow changes was correlated with the patterns of several cerebral networks including the default mode network. These findings suggest that hypothalamic blood flow response to systemic glucose levels can potentially be explained by regulatory activity. The response of extra-hypothalamic clusters followed a different time course and its spatial pattern resembled that of the default-mode network.